2020
DOI: 10.1080/09712119.2020.1754218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two probiotic preparations on growth performance, intestinal microbiota, nutrient digestibility and cytokine gene expression in broiler chickens

Abstract: This study was done to evaluate the effects of two dietary probiotic preparations (Bacillus subtilis and Bacillus licheniformis) on growth performance, intestinal microbiota, nutrient digestibility and cytokine gene expression in broiler chickens. A total of 180 male broiler chicks (one-day-old Ross 308 strain, average initial body weight = 40.05 ± 0.12) were used in a completely randomized design (CRD) composed of 3 treatments and 6 replicates. Experimental diets included: (1) basal diet (without additive), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 70 publications
1
23
1
Order By: Relevance
“…6). Our results confirm the findings of Hooge et al (15), who carried out research on broiler chickens fed with fodder with the addition of a probiotic preparation including Bacillus subtilis and the findings of Zaghari et al (39), who fed broiler chickens on a basal diet plus 0.5 (g/kg) diet B. licheniformis preparation (1 × 10 9 CFU/g). These showed greater weight gain and a lower feed conversion rate throughout the rearing period.…”
Section: Resultssupporting
confidence: 91%
“…6). Our results confirm the findings of Hooge et al (15), who carried out research on broiler chickens fed with fodder with the addition of a probiotic preparation including Bacillus subtilis and the findings of Zaghari et al (39), who fed broiler chickens on a basal diet plus 0.5 (g/kg) diet B. licheniformis preparation (1 × 10 9 CFU/g). These showed greater weight gain and a lower feed conversion rate throughout the rearing period.…”
Section: Resultssupporting
confidence: 91%
“…A comparative study showed that B. licheniformis and B. subtilis , both as probiotics, improved BWG, FCR, and production efficiency factor (PEF). However, the former species outperformed the later in improving BWG and PEF [ 67 ]. On the contrary, studies [ 13 , 36 , 47 ] showed no effect of probiotics supplementation on broiler growth performance.…”
Section: Growth Performancementioning
confidence: 99%
“…The probiotic supplementation of broilers with B. licheniformis and B. subtilis did not show a significant effect on the ileal and cecal microflora [ 67 ]. This non-significant effect on total aerobic and Salmonella count in the gut was also found when a mash diet supplemented with Lactobacillus acidophilus , L. casei , Enterococcus faecium , and Bifidobacterium thermophilus was fed to Ross 308 broiler chickens [ 93 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…It has been observed that many probiotic bacteria show a greater capacity to adhere to the chicken's intestinal mucosa than do pathogens and, therefore, displace them (Collado et al 2005). It has also been demonstrated that many probiotics favour the survival of beneficial bacteria such as Lactobacilli because they decrease intestinal pH (Olnood et al 2015a;Shini et al 2020b;Zaghari et al 2020). Lactic acid production is increased by B. amyloliquefaciens, which most probably explains the drop in ileum pH (Wu et al 2011;Salim et al 2013;Shini et al 2020b) associated with feeding this probiotic species.…”
Section: Modulation Of Intestinal Microbiotamentioning
confidence: 99%
“…New England pioneered the application of 'competitive exclusion' (Lloyd et al 1977;Soerjadi et al 1978) in Australia. Since then, many investigators have shown that probiotics can restore the composition of the gut microbiome, and introduce beneficial functions to microbial communities, and in doing so, they prevent or reduce gut inflammation and intestinal infection and improve bird performance (Eckert et al 2010;Mountzouris et al 2010;Cengiz et al 2015;Huff et al 2015;Latorre et al 2015;Park and Kim 2015;Forte et al 2016;Bai et al 2017;Pereira et al 2019;Yadav and Jha 2019;Shini et al 2020b;Zaghari et al 2020).…”
Section: Introductionmentioning
confidence: 99%